Revisiting the Taxonomy of Javan Philautus (Anura: Rhacophoridae), with the Description of a New Species - Herlambang, Alamsyah Elang Nusa; Gonggoli, Ade Damara; Racho, Asrael; Asti, Hastin Ambar; Cahyadi, Ganjar; Atmaja, Vestidhia Y.; Fauzi, Muhammad Alif; Eprilurahman, Rury; Hamidy, Amir (Zootaxa, 2026)
The genus Philautus comprises 52 recognized species, three of which are currently known from Java and are endemic to the island. We conducted extensive fieldwork across Central Java between 2017 and 2025 to reassess the taxonomy of Philautus in this understudied region. We clarified species boundaries and uncovered cryptic diversity within this genus by employing an integrative framework that combined morphological assessments, molecular phylogenetics, and bioacoustic analyses. Our results include a redescription of P. jacobsoni and the formal description of a newly identified montane species, Philautus candrageni sp. nov., from Mount Merapi. We also provide further insights into the taxonomic status of Philautus pallidipes. These findings reveal considerable taxonomic complexity and previously overlooked diversity within Java’s montane amphibian assemblages. They also underscore the importance of sustained integrative research and advocate for targeted conservation efforts for Philautus species across the island.